Search for resonances decaying to a pair of Higgs bosons in the b(b)over-barq(q)over-bar ' l nu final state in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2019)
A search for new massive particles decaying into a pair of Higgs bosons in proton-proton collisions at a center-of-mass energy of 13 TeV is presented. Data were collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 35.9 fb(-1). The search is performed for resonances with a mass between 0.8 and 3.5 TeV using events in which one Higgs boson decays into a bottom quark pair and the other decays into two W bosons that subsequently decay into a lepton, a neutrino, and a quark pair. The Higgs boson decays are reconstructed with techniques that identify final state quarks as substructure within boosted jets. The data are consistent with standard model expectations. Exclusion limits are placed on the product of the cross section and branching fraction for generic spin-0 and spin-2 massive resonances. The results are interpreted in the context of radion and bulk graviton production in models with a warped extra spatial dimension. These are the best results to date from searches for an HH resonance decaying to this final state, and they are comparable to the results from searches in other channels for resonances with masses below 1.5 TeV.
Keywords: Beyond Standard Model; Hadron-Hadron scattering (experiments); Higgs physics; PP COLLISIONS; INVARIANT; MODEL; MASS; WZ; ALGORITHMS; HIERARCHY; EXTENSION; LEPTONS; ZH